The Effect of Adding Ethanol Extract of Pomegranate Peel (Punica Granatum L.) on the Sun Protection Factor (SPF) Value of Sunscreen Cream Combination of Avobenzone and Octyl Methoxycinnamate - Julianty, Siti Muliani; Ginting, Ernawaty; Sudewi, Sudewi; Rizki, Fanny; Nadia, Syarifah; Saputri, Muharni (Indonesian Journal of Science and Pharmacy, 2024)
The compounds contained in pomegranate skin are phenolic acids, flavonoids, and tannins, including anthocyanidin, gallic acid, ellagic acid, ellagitannin, gallotanin, catechin, quercetin, which have antioxidant properties. The benefits of pomegranate peels are that they treat health problems and maintain beautiful skin. This research aimed to see the effect of adding pomegranate peel (Punica granatum L.) ethanol extract on the Sun Protection Factor (SPF) value of a combination of avobenzone and octyl methoxycinnamate sunscreen cream. This research was carried out using experimental methods. The formulation of sunscreen cream preparations uses pomegranate peel ethanol extract in various concentrations. The cream was evaluated to determine its Sun Protection Factor (SPF) value, organoleptic test, homogeneity, pH, emulsion type, and irritation test. The organoleptic test results showed that the cream produced in the blank had no odor and was white, while the cream with the addition of pomegranate peel ethanol extract had a distinctive smell and was brown. The emulsion type test shows the oil in the water type.  The addition of pomegranate peel ethanol extract to each formula increased the sun protection factor (SPF) value of sunscreen preparations. The average SPF value of each formula was FI 12.5956, FII 13.9673, FIII 16 .8205, FIV 17.9187, and FV 18.8437.